U-shaped Dural Flap: A Simple Method for Transcranial Skull Base Defect Repair—Technical Report - Ozdol, Cagatay; Aghayev, Kamran (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Accidental anterior skull base defects associated with surgery are difficult to treat. There are several methods for the repair, yet postoperative rhinorrhea can occur despite the closure. A 56-year-old female patient was admitted for the treatment of a paraclinoid internal carotid artery aneurysm. The surgery included removal of the anterior clinoid process, unroofing the optic canal, decompressing the optic nerve, and clipping the aneurysm. During the surgery, the planum sphenoidale was accidentally drilled and the nasal cavity exposed. The dural defect was repaired using a U-flap technique. No postoperative cerebrospinal fluid (CSF) rhinorrhea occurred in the patient, and she was discharged on postoperative day 3. On follow-up examination the patient did not have evidence of CSF leakage.
Keywords: CSF leakage; defect; dura; repair; skull base